PENGEMBANGAN E-MODUL BERBASIS APLIKASI WEB LIVEWORKSHEETS UNTUK MENINGKATKAN LITERASI SAINS - Gamal Titus Ade Putra; Arnelia Dwi Yasa; Farida Nur Kumala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by issues stemming from a lack of optimal technological innovation and a scarcity of learning resources to assist students. Through this study, the researcher aimed to produce a product, specifically the development of an E-Module integrated with scientific literacy attitudes on the topic of animal reproduction (oviparous, viviparous, and ovoviviparous) for grade 3 students. This research employed the R&D (Research and Development) method and utilized the 4D (Four D) model. The study involved trial subjects consisting of material experts, media experts, language experts, a teacher, and grade 3 students from SDN 5 Tambakasri Malang. Data collection in this research was conducted using instruments in the form of observation sheets, interview guides, and questionnaires. Based on the research results obtained, the feasibility test results from the media expert assessment percentage were 91.17%, which is in the highly feasible category. The percentage of material expert assessment results was 93%, also in the highly feasible category. The percentage of language expert assessment was 89.58%, included in the highly feasible category. Furthermore, the percentage of practicality assessment from the teacher's response was 93.75%, categorized as highly practical. The results obtained from the student questionnaire assessment yielded a percentage of 87.3%, included in the highly practical category. The effectiveness test was obtained with an N-Gain score of 0.64 with an average of 64.75, categorized as